LYAPUNOV EXPONENTIALLY STABILITY FOR SOME MODELS NONLINEAR PDEs (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to analyzing exponential stability of non-linear partial differentialequation using Lyapunov second method. We consider different models from heat and wavenon-linear equations in addition to 2×2 hyperbolic system with balance laws. We show theeffectiveness of the proposed methodology using some examples of different types ofnonlinear PDEs.